EVALUATION OF HUMORAL AND CELLULAR IMMUNE RESPONSES TO EIMERIA TENELLA OOCYST PROTEIN AS VACCINE TO BROILER - Suhair R. Al-Idreesi; Mahmoud Kweider; Mahmad M. Katranji (Basrah Journal of Veterinary Research)
To determine the type of immune response to oocyst vaccine in broiler against coccidiosis,broilers were vaccinated with two doses of prepared oocyst protein from the local strain ofEmeria tenella parasite. The vaccine was applied on 3rdand 16th day of age subcutaneously ata dose (25 μg per chicken), vaccinated birds were challenged at 30 day of age. Blood sampleswere collected at (7th, 28thand 39th) day of age. The immunogenicity of vaccine was studiedby using SDS-PAGE and Western blot. Fourteen polypeptides had been estimated moreimmunogenic after probing with immunized chicken serum at 39th days of age, theirmolecular weight are (167.8, 114.5, 83.4, 78.2, 73.5, 53.3, 44.1, 38.8, 36.4, 28.2, 20.5, 18,14.9and 13.9) KD. In addition, the levels of ˠ -IFN and IL-4 were estimated in the serum ofimmunized chickens by using ELISA kits. The results demonstrated two types of immunity,cellular and humoral responses against E.tenella oocyst vaccine.